Design and development of an IoT-based burner-wet scrubber system for mitigating emissions from agricultural waste combustion - Ayu Wulandari; Ega Nugraha Firdaus; Ravy Rahadi (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: This study is situated in the context of increasing agricultural waste generation and the continued reliance on open burning practices in rural farming areas, which contribute to air pollution, greenhouse gas emissions, and occupational exposure risks. The aim of this study is to design and examine a transitional engineering solution in the form of an Internet of Things (IoT)-based Burner-Wet Scrubber system to support controlled biomass combustion and emission mitigation in agricultural waste processing. Previous studies have primarily focused on composting and agricultural waste reuse, with limited attention to practical solutions for small-scale farming. Methods: This study applies an engineering-experimental approach consisting of reverse engineering analysis, system design, prototype development, and pilot testing under controlled biomass combustion conditions. Data were collected through IoT sensor monitoring of combustion temperature and exhaust flow behavior, accompanied by observational assessment of particulate dispersion and functional performance of the wet scrubber unit. Findings: The proposed system is capable of processing 100 to 875 kg of agricultural waste per cycle while producing a char yield of 25 to 35% under controlled pyrolysis with an electrical power consumption of approximately 1200 W. The results show that the system operates effectively as an integrated combustion and filtration unit, characterized by more stable combustion conditions inside the burner chamber and a visible reduction in particulate dispersion compared to open burning conditions, while the monitoring interface facilitates transparent process observation and operational evaluation. These findings support the theoretical position of the system as an engineering intervention that aligns environmental mitigation objectives with practical field conditions. Conclusion: The study concludes that an IoT-based Burner-Wet Scrubber system has the potential to serve as a feasible, adaptive, and community-scale emission mitigation alternative for agricultural waste combustion. Novelty/Originality of this article: The novelty of this study lies in integrating a controlled burner, wet scrubber, and real-time IoT monitoring for smallholder agricultural applications.